STRATEGI KOMUNIKASI KEPALA SEKOLAH DALAM MENINGKATKAN HUBUNGAN HARMONIS - Zahra Nabila Iqbal; Abdul Fattah Nasution (Jurnal Manajemen Pendidikan, 2026)
Effective communication between principals and teachers plays an important role in creating harmonious relationships within the school environment. This study aims to analyze the principal’s communication strategies in improving harmonious relationships at SMA Swasta Budisatrya. The research employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research informants included the principal, vice principal, and teachers. The findings revealed that the principal implemented communication strategies that were open, two-way, participatory, and family-oriented. Communication was carried out intensively through formal and informal activities such as meetings, briefings, discussions, and daily interactions. The principal also involved teachers in the decision-making process, which created a comfortable and harmonious working relationship. These communication strategies contributed to improving cooperation, strengthening interpersonal relationships, minimizing conflicts, and supporting the effectiveness of school organization. Supporting factors included openness in communication, intensity of interaction, and the ability to adjust communication styles, while obstacles such as differences in character and perspectives were resolved through deliberation and intensive communication.